Reaktsiya serdechno-sosudistoj sistemy na razdrazhenie vestibulyarnogo apparata u predstavitelej sportivnoj gimnastiki - Kiryalanis, P.; Laparidis, K.; Sofiadis, N. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The purpose of the present study was to investigate the reaction of the cardiovascular system (K.S.) after the imitation of the balance system (B.S.). The study group was 84 (n=84) male and female gymnasts (group A) and 97 (n=97) boys and girls of the control group (group B). The average age of the gymnasts was 12,01 ± 3,15 and for the control group was 11,68 ± 3,23.years. For the imitation of the balance system (B.S.), has been used the Barany chair, where the subjects with closed eyes and with the head bent in front in a position of 30O, were rotated (15 rotation/30 sec alternately right-left) for a total time duration of 3 min. The imitation of B.S. caused significant changes in both groups (A) and (B) to the blood pressure system, but the results also indicated that the subjects of the group (A) had a better-trained B.S. The results also indicates that there are difference between males and females, with the females having better adapted B.S., than the male, especially in the gymnastics group (A).